Genotoxic effects of alpha-endosulfan and beta-endosulfan on human HepG2 cells. - Lu, Y (2000)
alpha-Endosulfan and ss-endosulfan are isomers of endosulfan, a pesticide used worldwide. In this study, we examined the genotoxicity of [alpha]- and ss-endosulfan in vitro with a HepG2 cell line. We used sister chromatid exchanges (SCE), micronuclei (MN), and DNA strand breaks as detected by single-cell gel electrophoresis (SCG) assays as biomarkers to judge the genotoxicity of [alpha]- and ss-endosulfan at concentrations from 1 times 10(-12) M to 1 times 10(-3) M. After treating HepG2 cells for 48 hr with ss-endosulfan, SCE showed a significant increase at concentrations from 1 times 10(-7) M to 1 times 10(-5) M, and MN showed a significant increase at concentrations from 5 times 10(-5) M to 1 times 10(-3) M. [alpha]-Endosulfan failed to show significant effects in both the SCE and MN assays. After treating HepG2 cells with [alpha]- or ss-endosulfan for 1 hr, DNA strand breaks were significantly induced by [alpha]-endosulfan at concentrations from 2 times 10(-4) M to 1 times 10(-3) M, and by ss-endosulfan at 1 times 10(-3) M. The results of this study suggest that both [alpha]- and ss-endosulfan are genotoxic to HepG2 cells and that the genotoxicity of ss-endosulfan seems stronger than that of [alpha]-endosulfan.